Drospirenone‐Containing Oral Contraceptives and Risk of Adverse Outcomes After Myocardial Infarction. Issue 3 (2nd March 2013) - Karabay, Can Yucel; Kocabay, Gonenc; Oduncu, Vecih; Kalayci, Arzu; Guler, Ahmet; Karagöz, Ali; Candan, Ozkan; Basaran, Ozcan; Zehir, Regayip; İzgi, Akın; Esen, Ali Metin; Kırma, Cevat
<x xml:space="preserve">Abstract</x> Background The association between oral contraceptives (OC) and myocardial infarction remains controversial. The new generation contraceptive Yasmin (30 µg ethinyl estradiol and 3 mg drospirenone) has a lower estrogen and newer progestin component. To date, there are no data available for the myocardial infarction risk and outcome for drospirenone. We aimed to investigate the effect of Yasmin use on cardiovascular outcomes in patients with acute ST segment elevation myocardial infarction (STEMI) undergoing primary angioplasty. Methods We retrospectively evaluated 1851 patients who underwent primary angioplasty for acute STEMI. Of them, 440 female patients (23.8%) composed the study population and 12 female (2.7%) were taking the oral contraceptive‐Yasmin at the time of infarction. Patients were divided into two groups based on their age (≥50 (n = 339) and <50 years old). Patients under 50 years‐old (n = 101) were separated into two groups according to use of OC therapy (OC (+) group n = 12; OC (−) group n = 89). Results Patients who were older than 50‐year‐old were more likely to have comorbid conditions like diabetes mellitus and hypertension than other groups. Current smoking status was significantly higher in OC (+) group than OC (−) group (P = 0.007). There was a significant difference in favour of OC (+) group when compared with OC (−) group for the increased angiographic thrombus burden according to both TIMI and Yip classification (P = 0.045 and P = 0.029, respectively). The incidence of final TIMI 3 flow and post‐procedural complete ST resolution were significantly lower in OC (+) group (P = 0.019, P = 0.002, respectively). In multivariate logistic regression analysis, use of OC was found to be an independent predictor of high grade thrombus burden (OR 5.13, 95% CI 1.07–24.60, P = 0.04). Conclusion This is the first study to evaluate the myocardial infarction risk and its subsequent clinical sequelae in women having a STEMI while taking the OC‐Yasmin. Women on the oral contraception Yasmin, who underwent coronary revascularization had a lower post‐procedural complete ST resolution and worse left ventricular function. Furthermore, OC use with Yasmin is an independent predictor of a high‐grade thrombus burden. © 2013 Wiley Periodicals, Inc.